Extraktivt våld och urfolks koppling till mark - Sehlin MacNeil, Kristina; Inga, Niila (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2019)
Extractive violence on Indigenous peoples’ lands is not only a violation against nature but also a violation against Indigenous peoples who experience close connection to land. This paper explores how Australian Aboriginal people and reindeer herding Sámi in Sweden connect with their lands and how these connections are threatened by extractivism. Extractive activities cause destruction of reindeer grazing lands and interrupts reindeer migratory patterns. The reindeer is the backbone of Sámi history, culture and society and is the foundation for language and traditional Sámi livelihoods. Reindeer herding Sámi communities in Sweden depend on the reindeer to exercise their rights to land, as the rights are connected to reindeer grazing. In Australia, where Indigenous peoples can be awarded certain land rights through Native Title, they are nonetheless still fighting to become recognized in the Australian constitution. Many Indigenous Australians also desperately work to save sacred sites from destruction due to extractivism. This creates complex dynamics between connection to land, rights and extractivism on Indigenous lands.